INCREASING THE WEAR RESISTANCE OF STEEL GAS-THERMAL COATINGS BY ELECTROCONTACT TREATMENT - Lopata, Oleksandr; Lopata, Vitaly; Solovykh, Yevhen; Posviatenko, Nataliia (Problems of Friction and Wear, 2024)
The most promising method of increasing the wear resistance of low-resource parts of machines and mechanisms is the formation of wear-resistant layers on their working surfaces from the most accessible and low-cost materials for coatings in combination with technologies for applying coatings and their subsequent processing. The article proposes a method for creating parts with wear-resistant coatings, combining flame and (or) electric arc spraying of steels of ferritic and martensitic classes and their subsequent electrical contact processing. When creating coatings, it is proposed to use an approach based on the creation and targeted controlled use of deformation-induced structural-phase transformations and metastable states during the application of gas-thermal coatings and their processing, which ensure an increase in microhardness, wear resistance, physical-mechanical and operational properties. A new approach to obtaining gas-thermal steel coatings on low-alloy steels with increased wear resistance is proposed, which is based on the creation and purposeful controlled use of deformation structural-phase γ→α transformations and metastable states by means of temperature-force influence during their electrical contact processing; The relationship between the physico-mechanical properties of steel coatings and structural-phase γ→α transformations in them is established, and it is shown that the level of these properties, controlled by the degree of saturation of the martensitic α-phase with carbon, increases with an increase in the content of carbon and carbide inclusions in steels.